Comparison of Analgesic Effect of Agnogol with Mefenamic Acid in the Treatment of Primary Dysmenorrhea - Masoumeh Delaram; Zahra Sadeghian; Neda Parvin; Afsaneh Kazemiyan; Sahand Shams (Golestan University of Medical Sciences, 2015)
Background and Objective: Primary dysmenorrhea is one of the most common complaints among women in reproductive age in that about half of young women suffer from dysmenorrhea. Nowadays, many people have a tendency to use a traditional medicine for dysmenorrhea. Hence, we aimed to compare the analgesic effect of Agnogol and Mefenamic acid in the treatment of primary dysmenorrhea.  Material and Methods: This clinical trial was conducted on 44 women with primary dysmenorrhea referred to Hajar hospital in Shahrekord. The participants were randomly allocated to two groups of Agnogol (n=23) to use one 3.2 mg Agnogol pill for three times a day and Mefenamic Acid (n=21) to use 250 mg Mefenamic acid every 8 hours a day for three days. The pain severity was detected by Visual Analogue Scale. We used Independent and Paired t test for comparing the means of quantitative variables and Chi Square for qualitative variables ( P<0.05 ).  Results: Considering age, menstrual duration, menstrual interval, and pain severity score, there was no significant difference in two groups at the beginning of the study (P>0.05). After intervention, a significant reduction was found in the mean of pain score over time in both Agnogol (P<0.001) and Mefenamic acid (P0.05).  Conclusion: Given the same effect of Agnogol in mitigating dysmenorrhea, we recommend it as an appropriate alternative for Mefenamic acid.